Change From Law Number 4 Year 2009 to Law Number 3 Year 2020 in Environmental Obligations and Good Mining - Shan Riwanto Utomo; Tri Hayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Mining is an important thing for the world, which cannot be separated from the environment that is the object in it. In the amendments to the new law, namely Law Number 3 of 2020 concerning amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, there are regulations regarding environmental obligations and good mining principles. The number of mining companies that do not carry out reclamation has attracted the attention of many parties. The distribution of the authority of the central and local governments is also unstructured with many local governments' powers being amputated by the central government. The scope of the research is environmental problems such as reclamation studies, post-mining and good mining rules regarding the change from Law 4/2009 to Law 3/2020 and ineffective supervision in the implementation of Mining Business activities. The approach taken is using a normative juridical method based on an analysis of normative law. The distribution of authority related to supervision should be shared with the local government so that good mining rules can be perfectly realized. In implementing good mining rules, the government as the issuer of Mining Business Permits should be able to involve the community around the mine more because the role of the community around the mine is also necessary to maintain the ecosystem and environmental sustainability. Environmental responsibility must be increased where the role of mining corporations should not be reduced by choosing only reclamation or post-mining activities.